Enrichment of a denitratating microbial community through kinetic limitation. (March 2022) - Baideme, Matthew; Long, Chenghua; Chandran, Kartik
Graphical abstract: Highlights: Kinetic limitation was used to optimize denitratation performance. Distinctly different microbial ecologies were found at different SRTs. A microbial community with significantly lower nir gene transcripts was favored. Kinetic limitation contributions to NO2 – accumulation were identified. Abstract: Denitratation, or the intentionally engineered accumulation of nitrite (NO2 – ) from selective reduction of nitrate (NO3 – ), can be combined with downstream anammox to reduce chemical and energy use associated with conventional nitrification and denitrification. This study aimed to enrich a denitratating microbial community capable of significant NO2 – accumulation by applying added kinetic limitation to an already stoichiometrically-limited, glycerol-driven denitratation process. Operation at solids residence time, SRT=3.0 d, resulted in optimal denitratation performance and a microbial community dominated by NO3 – -respirers, noted by one order of magnitude lower total copy numbers of nirS and nirK gene transcripts compared to longer SRTs. Selective NO3 – reduction to NO2 – was achieved at all SRTs although longer SRTs (less kinetic limitation) supported microbial communities more capable of full denitrification as described by a lower NO2 – accumulation ratio (NAR=42±5%) and higher steady-state nitrous oxide (1.5 mg/L N2 O-N) accumulation. Shorter SRTs (more kinetic limitation) led to higher observed yields (Y=0.63 mg-COD/mg-COD) with more electrons dedicated for cell synthesis (fs =0.56±0.10), which potentially contributed to the accumulation of NO3 – . Enrichment of a denitratating-dominant microbial community by optimizing kinetic limitation operating parameters could support significant NO2 – accumulation and reduce chemical and energy use for biological nitrogen removal when combined with downstream anammox.